ECONOMIC ASPECTS OF LIFELONG LEARNING IN LATVIAN REGIONS - Sannikova, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
despite the extreme urgency of lifelong learning in the era of knowledge economy, employers in Latvia’s regions are not active investors in the training of their employees, and individuals are not eager to actively educate themselves throughout their lives, mentioning the expensiveness of lifelong learning – unlike in the majority of EU Member States – as the key reason. Therefore, one can identify the discrepancy between the political priorities and the actual situation. The author, following the idea of Latvia’s scientist A.Jaunzems to perceive knowledge purely economically – as a product of the education market – developed this idea further by examining the knowledge market in Latvia’s regions in regard to its institutional “casing”, i.e. lifelong learning. The research findings show that the regional specifics of lifelong learning in Latvia are determined by the fact that Latvia’s regions are in different stages of economic development.